Original paperGrain dust originating from organic and conventional farming as a potential source of biological agents causing respiratory diseases in farmers - Żukiewicz-Sobczak, Wioletta A.; Cholewa, Grażyna; Krasowska, Ewelina; Chmielewska-Badora, Jolanta; Zwoliński, Jacek; Sobczak, Paweł (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Agricultural producers are exposed to a number of different health risks associated with their work environment. Aim: The objective of the study was to assess the degree of colonization by fungi in terms of quantity and in terms of variety of species the samples taken from the settled dust from combine threshing of rye cultivation from organic and conventional farms in the Province of Lublin. Material and methods: This paper is a preliminary quantitative assessment of the species of fungi colonizing the samples of settled dust collected during combine threshing from organic and conventional farms in the Province of Lublin. One of the stages of the project was the classification of biosafety BSL (biosafety level) of selected isolates and API ZYM tests to evaluate the potential ability of isolates to cause adverse health effects. To determine the concentration and composition of fungi in collected samples plate dilution method was used with two media: Malt Agar and Potato Dextrose Agar. Results : Most commonly isolated fungi in settled dust samples collected during combine threshing from organic farms, on PDA medium were: Alternaria alternata and Aureobasidium pullulans. Cultures on MA medium were dominated by Alternaria alternata, Mycelia sterilia and Fusarium poae. In samples of dust from conventional crops, the predominant species was Alternaria alternata on PDA medium and on MA medium. Conclusions : The obtained results show a potential risk of people involved in agricultural work.